Central venous stenosis after subclavian versus internal jugular dialysis catheter insertion (CITES) in adults in need of a temporary central dialysis catheter: study protocol for a two-arm, parallel-group, non-inferiority randomised controlled trial - Ola Borgquist; Leila Naddi; Gracijela Božović; Matthias Hellberg; Martin Annborn; Fredrik Sjövall; Maria Adrian; Eva Hettinger; Pia Sjöberg; Thomas Kander (Trials, 2023)
Abstract Background The right internal jugular vein is currently recommended for temporary central dialysis catheters (tCDC) based on results from previous studies showing a lower incidence of central vein stenosis compared to the subclavian vein. Data is however conflicting, and there are several advantages when the subclavian route is used for tCDCs. This prospective, controlled, randomised, non-inferiority study aims to compare the incidence of post-catheterisation central vein stenosis between the right subclavian and the right internal jugular routes. Methods Adult patients needing a tCDC will be included from several hospitals and randomised to either subclavian or internal jugular vein catheterisation with a silicone tCDC. Inclusion continues until 50 patients in each group have undergone a follow-up CT venography. The primary outcome is the incidence of post-catheterisation central vein stenosis detected by a CT venography performed 1.5 to 3 months after removal of the tCDC. Secondary outcomes include between-group comparisons of (I) the patients’ experience of discomfort and pain, (II) any dysfunction of the tCDC during use, (III) catheterisation success rate and (IV) the number of mechanical complications. Furthermore, the ability to detect central vein stenosis by a focused ultrasound examination will be evaluated using the CT venography as golden standard. Discussion The use of the subclavian route for tCDC placement has largely been abandoned due to older studies with various methodological issues. However, the subclavian route offers several advantages for the patient. This trial is designed to provide robust data on the incidence of central vein stenosis after silicone tCDC insertion in the era of ultrasound-guided catheterisations. Trial registration Clinicaltrials.gov; NCT04871568. Prospectively registered on May 4, 2021.